Role of Cooperatives for Sustainable Livelihood in Bagmati Province, Nepal (The International Research Journal of Management Science, 2021)
The study aims in analyzing the role of cooperatives for sustainable livelihood of people in Bagmati Province (3), in Nepal. Cooperatives areconsidered to be the third pillar of Nepalese economy. The ongoing literature suggests that the cooperative movements have relationship with quality of work life of people and poverty reduction. Nepal is developing her future prosperity and growth. Hence, the study has pointed out the gap in the literature and the practice. The descriptive and analytical research designs have been adopted in the study. The secondary source has been used to collect the data. The MS Excel Software has been used to tabulate and analyze the data. The study found that the cooperative movement is more prone in Bagmati and Gandaki Province that resulted decrease in poverty rate and the increase in the employment rate. The activities of the cooperatives in the investment in share, saving, lending and employment creation hadcontributed in the sustainable livelihood of people in Bagmati Province, Nepal. .